Analisis Kinerja Mesin Chiller AKL5500AV Pada PT. XXX - Suriaman, Irwan; Dede, Dede Ardi Rajab; Daniel Pernando Manulang (Jurnal Teknologika, 2023)
The industrial world is increasingly advanced, especially in the field of air conditioning technology, this is influenced by the development of information systems that are very fast and dynamic. Industries compete to use technology to make their operations more efficient. The cooling machine has made a lot of progress. Currently, various refrigeration machines are not only used to cool rooms and vehicles, but refrigeration machines are also needed to cool the products produced. One of the advances in cooling machine technology is the AKL5500AV chiller machine. This machine is used to cool PBL plastic products produced. The temperature generated by this cooling machine is unstable, so it affects the production results at PT. XXX. This test is carried out by analyzing temperature indicators and wind pressure indicators at different hours and different temperature conditions. To get maximum results, testing is carried out on the chiller machine. The purpose of this test is to see the performance of the chiller and find out the COP value of the chiller. The test results show that the Coefficient of performance (COP) and Performance factor (PF) values produced are not in accordance with the standards. Chiller's COP value was 3.04 and PF was 4.04. This is of course an input that in order to maintain the performance of the cooling machine, maintenance of the chiller machine must be maintained.